Proposed Optimal Fluoroscopic Targets for Cooled Radiofrequency Neurotomy of the Sacral Lateral Branches to Improve Clinical Outcomes: An Anatomical Study. Issue 10 (23rd November 2017) - Stout, Alison; Dreyfuss, Paul; Swain, Nathan; Roberts, Shannon; Loh, Eldon; Agur, Anne
Abstract: Background: Current sacroiliac joint (SIJ) cooled radiofrequency (RF) is based on fluoroscopic anatomy of lateral branches (LBs) in three specimens. Recent studies confirm significant variation in LB positions. Objectives: To determine if common fluoroscopic needle placements for cooled SIJ RF are adequate to lesion all S1–3 LBs. If not, would different targets improve lesion accuracy? Methods: The LBs of 20 cadavers were dissected bilaterally (40 SIJs), and 26 G radiopaque wires were sutured to the LBs. With a 10-mm radius ruler centered at each foramen, standard targets were assessed, as judged by a clockface on the right, for S1 and S2 at 2:30, 4:00, and 5:30 positions and at S3 at 2:30 and 4:00. Mirror image targets were assessed on the left. Assuming an 8-mm lesion diameter, the percentage of LBs that would not be ablated for each level was determined. Imaging through the superior end plate of S1 was compared against segment specific (SS) imaging. Results: Nine point four percent of LBs would not be ablated at S1 vs 0.99% at S2 vs 35% at S3, and 60% of the 40 SIJs would be completely denervated using current targets. SS imaging did not improve results. Alternate target locations could improve the miss rate to 2.8% at S1 and 0% at S3 and would ablate all LBs in 95% of SIJs. Conclusions: Using a conservative 8-mm lesion measurement, contemporary cooled RF needle targets are inadequate to lesion all target LBs. Modifications to current targets are recommended to increase the effectiveness of the procedure.